Critical patterns associated with vehicle-pedestrian hit-and-run casualty injury severity under different weather conditions: An association rule mining approach - Reuben Tamakloe; Emmanuel Kofi Adanu (IATSS Research)
Vehicle-pedestrian hit-and-run crashes have grave consequences as the pedestrian casualty is left at the crash scene, leading to delays in emergency response. Research indicates that prevailing weather conditions are pivotal in influencing these crashes. Nonetheless, there exists a substantial gap in understanding the diverse associations of contributing factors that impact the severity of pedestrian injuries in vehicle-pedestrian hit-and-run crashes under varying weather conditions. This paper extensively examines the intricate patterns of critical factor associations influencing the pedestrian casualty injury severity in vehicle-pedestrian hit-and-run collisions in Ghana, differentiating between clear and inclement weather conditions. Leveraging historical crash data, this research employs the robust Association Rule Mining tool to unveil the relationships between key crash factors and their outcomes. The association rules extracted from the data reveal that specific factors consistently influence injury outcomes in vehicle-pedestrian hit-and-run crashes, regardless of weather conditions. However, there are distinct patterns of factors contributing to fatal and severe injuries in these crashes that vary depending on the prevailing weather conditions. Hit-and-run crashes resulting in fatal and severe pedestrian injuries are primarily associated with males and are notably correlated with factors like pedestrian crossings, late and early morning hours, the absence of traffic control measures on median-separated motorways, and good urban roads, regardless of prevailing weather conditions. During clear weather conditions, fatal/severe injuries tend to occur in daylight conditions, primarily on roadways devoid of shoulders, and involve older pedestrians crossing the road. Conversely, for inclement weather conditions, these crashes are more prone to occur during nighttime hours on unlit roads, often involving younger pedestrians walking along the road's edge. The reduction of fatal/severe injury hit-and-run crashes involving vehicles and pedestrians can be effectively tackled by eliminating or improving the critical factors pinpointed in the extracted rules. The study underscores the urgency of policy recommendations to mitigate fatalities resulting from vehicle-pedestrian hit-and-run crashes, emphasising the need for stricter legislation, heightened enforcement measures, increased awareness of pedestrian safety, enhanced driver training, and infrastructure upgrades. By acting on these insights, a significant stride can be made in curbing the alarming rates of vehicle-pedestrian hit-and-run fatalities.